Extending single molecule spectroscopic techniques to multi-particle systems of semiconductor nanocrystals - Shepherd, Douglas Parker, author; Gelfand, Martin Paul, advisor; Van Orden, Alan K., advisor; Roberts, Jacob Lyman, committee member; Prieto, Amy Lucia, committee member (Colorado State University. Libraries, 2011)
This dissertation describes the application of single molecule spectroscopic techniques to individual semiconductor nanocrystals (NCs), small clusters of NCs, and NCs used as the light harvesting layer in sensitized solar cells. We first examine how coupling between close-packed NCs may alter their photophysical properties by studying isolated NCs and small clusters of NCs via single molecule time-correlated single-photon counting, from which fluorescence intensity trajectories, autocorrelation functions, decay histograms, and lifetime-intensity distributions have been constructed. These measurements confirm that NC clusters exhibit unique photoluminescence behavior not observed in isolated NCs. In particular, the NC clusters exhibit a short-lifetime component in their photoluminescence decay that is correlated with low photoluminescence intensity of the cluster. A model based on radiative energy transfer to NCs within a cluster that have smaller energy gaps, combined with independent blinking for the NCs in a cluster, accounts for the main experimental features. This energy transfer may lead to energy sinks when an excitation is transferred to a NC that is in the off state. We then examine a model photovoltaic system where a sub-monolayer film of NCs is chemically coupled to a single crystal semiconductor (TiO2 or ZnO) substrate through a variety of capping ligands. Again, utilizing time-correlated single photon counting and internal photon conversion efficiency we have studied both the photoluminescence intensity, photoluminescence decay time, and sensitized photocurrents. We find that for all configurations of capping ligands and substrate the photoluminescence decay rate is quenched compared to the free NCs in solution; whereas, only the short chain capping ligands that promote electron coupling to the substrate produce photocurrents. The longer chain capping groups both inhibit the electron injection and promote NC clustering on the surface where interactions between the individual NCs or the NCs and substrate alter the radiative rate. This result confirms that the possibility of NC clusters leading to a loss of energy due to inter-NC coupling is present in devices and warrants further study.